Profile of the faculty in teacher education some issues and concerns - Savellano, Julieta M. (1992)
A picture of a typical teacher of teachers is presented considering such factors as preservice preparation, specialization, actual teaching, research and extension experiences and their non-teaching responsibilities. In the end, issues and concerns as well as a few recommendations for improvement are discussed.
Keywords: Faculty -- Longitudinal studies